From Bismarck to Beveridge: The other pension reform in Spain - J. Ignacio Conde-Ruiz; Clara I. González (SERIEs - Journal of the Spanish Economic Association, 2016)
Ageing is the major challenge for the PAYG pension systems in developed countries. Most of them are undergoing reforms in order to adapt to the new demographic reality. The package of reforms implemented includes increasing the retirement age, reducing the replacement rate, or introducing a sustainability factor linking pension to life expectancy. The aim of this paper is to analyse the potential consequences of a different type of reform that is at a very incipient stage in Spain but that could have a significant impact if it were fully implemented. This reform, called 'silent reform' because it is imperceptible to citizens in its early stages, basically consists in increasing maximum pensions in line with inflation instead of wage or productivity growth. This policy is reducing the replacement rate only for high earning workers and increasing the redistributive component of the system. This paper is the first to quantify and evaluate the potential consequences of this type of reform in Spain. We have used an accounting model with heterogeneous agents and overlapping generations in order to project pension expenditure for the next six decades. The results show that this type of reform could potentially contain future expenditure but at the cost of changing the nature of the pension system from a contributory or Bismarckian-type system into a pure redistributive pension system or Beveridgean-type one.
Keywords: H55; J11; J26; 330; Ageing; Spanish pension system; Reform; Sustainability; Accounting projection model